All-solid-state secondary battery and method for producing same

By using a sulfide-based solid electrolyte layer with controlled gap rates, the battery achieves enhanced load characteristics and uniform reactions, addressing the performance issues in existing all-solid secondary batteries.

JP7624322B2Active Publication Date: 2025-01-30MAXELL LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021022874
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-02-16
Publication Date
2025-01-30
Estimated Expiration
2041-02-16

AI Technical Summary

Technical Problem

Existing all-solid secondary batteries face challenges in achieving optimal load characteristics due to high gap rates in the solid electrolyte layer, which can lead to non-uniform reactions and reduced performance.

Method used

The battery design incorporates a sulfide-based solid electrolyte layer with a gap rate of 3% or less and a ratio of larger gaps of 10% or less, achieved through high-pressure pressing of solid electrolyte particles between the positive and negative electrodes, ensuring uniform reaction distribution.

Benefits of technology

This configuration results in a solid secondary battery with improved load characteristics, enabling efficient and uniform battery reactions, enhancing energy density and reliability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007624322000002
    Figure 0007624322000002
  • Figure 0007624322000003
    Figure 0007624322000003
  • Figure 0007624322000004
    Figure 0007624322000004
Patent Text Reader

Abstract

To provide an all-solid secondary battery superior in load characteristic, and a manufacturing method thereof; the present invention relates to the goal 7, "Affordable and clean energy" and the goal 12, "Responsible consumption and production" of Sustainable Development Goals.SOLUTION: An all-solid secondary battery of the invention comprises a positive electrode, a negative electrode, and a solid electrolyte layer containing a sulfide-based solid electrolyte. The solid electrolyte layer has a porosity of 3% or less; in all the pores, pores larger than 1×10-2 μm2 account for 10% or less. The solid electrolyte layer can be obtained by e.g. the step of compression forming a layered collection of sulfide-based solid electrolyte particles with a surface pressure of 1000 MPa or more.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an all-solid-state secondary battery having excellent load characteristics and a method for manufacturing the same. [Background technology]

[0002] In recent years, with the development of portable electronic devices such as mobile phones and notebook personal computers, and the practical application of electric vehicles, there has been a demand for small, lightweight secondary batteries with high capacity and high energy density.

[0003] Currently, lithium secondary batteries that can meet this requirement, especially lithium ion secondary batteries, use lithium cobalt oxide (LiCoO 2 ), lithium nickel oxide (LiNiO 2 In these batteries, a lithium-containing composite oxide such as Cr-Al-Nb-Fe-O-Pb is used, graphite or the like is used as the negative electrode active material, and an organic electrolyte solution containing an organic solvent and a lithium salt is used as the non-aqueous electrolyte.

[0004] With the further development of devices that use lithium-ion secondary batteries, there is a demand for lithium-ion secondary batteries with longer life, higher capacity, and higher energy density.In addition, there is a high demand for the reliability of lithium-ion secondary batteries with longer life, higher capacity, and higher energy density.

[0005] However, the organic electrolyte used in the lithium ion secondary battery contains an organic solvent, which is a flammable substance. In addition, with the recent trend toward higher energy density of the lithium ion secondary battery and an increase in the amount of organic solvent in the organic electrolyte, there is a demand for even higher reliability of the lithium ion secondary battery.

[0006] In the above circumstances, all-solid-state lithium secondary batteries that do not use organic solvents (all-solid-state secondary batteries) are attracting attention. All-solid-state secondary batteries use a solid electrolyte that does not use organic solvents instead of the conventional organic solvent-based electrolytes.

[0007] Various improvements have been attempted for the all-solid-state secondary battery. For example, Patent Document 1 shows that a porosity of a solid electrolyte layer is 10% or less, and a surface roughness Rz1 of a positive electrode layer and a surface roughness Rz2 of a negative electrode layer satisfy a relationship of Rz1+Rz2≦25, thereby suppressing a short circuit between the positive electrode layer and the negative electrode layer.

[0008] In Patent Document 1, it is preferable that the thickness of the solid electrolyte layer is 20 μm or less from the viewpoint of improving the energy density of the battery, and the unevenness of the positive electrode layer surface and the negative electrode layer surface is reduced to prevent the positive electrode layer and the negative electrode layer from contacting each other, and the porosity of the solid electrolyte layer is reduced to suppress the growth of dendrites, thereby preventing a short circuit between the positive electrode layer and the negative electrode layer even when the solid electrolyte layer is thinned as described above.

[0009] In Patent Document 1, a positive electrode green sheet, a negative electrode green sheet, and an electrolyte green sheet, each of which contains oxide glass and an acrylic binder, are stacked and heated at 315°C for 10 hours to remove the acrylic binder contained in each green sheet of the stack. The stack is then pressure-sintered at 400°C and a pressure of 30 MPa for 10 minutes to convert the oxide glass contained in each green sheet of the stack into oxide glass ceramics (a mixture of oxide glass and oxide crystals), and a coin-type all-solid-state battery is assembled. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] Patent No. 6729796 Summary of the Invention [Problem to be solved by the invention]

[0011] In the all-solid-state battery of Patent Document 1, the porosity of the solid electrolyte layer can be reduced, but as shown in FIG. 5, relatively large voids are formed, which tends to cause the battery reaction to become non-uniform, resulting in a problem that sufficient load characteristics cannot be obtained.

[0012] Therefore, an object of the present invention is to provide an all-solid-state secondary battery having excellent load characteristics and a manufacturing method thereof. [Means for solving the problem]

[0013] The all-solid-state secondary battery according to an embodiment of the present invention includes a positive electrode, a negative electrode, and a solid electrolyte layer containing a sulfide-based solid electrolyte disposed between the positive electrode and the negative electrode. The porosity of the solid electrolyte layer calculated from a scanning electron microscope (SEM) image of the central portion of a cross section of the solid electrolyte layer is 3% or less, and the porosity of the solid electrolyte layer is 1×10 4 or less of all voids in the region. -2 μm 2 The proportion of larger voids is 10% or less by number.

[0014] The method for producing the all-solid-state secondary battery includes a step of pressurizing and molding a layered assembly of sulfide-based solid electrolyte particles at a surface pressure of 1000 MPa or more. Effect of the Invention

[0015] According to the present invention, it is possible to provide an all-solid-state secondary battery having excellent load characteristics and a manufacturing method thereof. [Brief description of the drawings]

[0016] [Figure 1] FIG. 1 is a cross-sectional view illustrating an example of an all-solid-state secondary battery according to an embodiment of the present invention. [Diagram 2] FIG. 13 is a diagram showing a binarization threshold value in a tone distribution histogram of an SEM image. [Diagram 3] 1 is a graph showing the distribution of void sizes in a solid electrolyte layer. [Figure 4] 1A and 1B are diagrams showing SEM images that have been processed and divided into low-brightness and high-brightness areas, where (a) is an image of Example 1 and (b) is an image of Comparative Example 1. FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] The all-solid-state secondary battery according to an embodiment of the present invention includes a positive electrode, a negative electrode, and a solid electrolyte layer containing a sulfide-based solid electrolyte disposed between the positive electrode and the negative electrode. The porosity of the solid electrolyte layer calculated from a scanning electron microscope (SEM) image of the central portion of a cross section of the solid electrolyte layer is 3% or less, and the porosity of the solid electrolyte layer is 1×10 4 or less of all voids in the region. -2 μm 2 The proportion of larger voids is 10% or less by number.

[0018] In the all-solid-state secondary battery, the solid electrolyte layer contains a sulfide-based solid electrolyte. The porosity of the central part of the cross section of the solid electrolyte layer (a region including the width direction center and the thickness direction center of the cross section of the solid electrolyte layer) calculated from an SEM image is 3% or less, and is 1×10 -2 μm 2 The ratio of larger voids is 10% or less in terms of number ratio. In general, the porosity near the ends in the width direction of the solid electrolyte layer tends to be larger than the porosity in the center. By forming a solid electrolyte layer containing a sulfide-based solid electrolyte so that the porosity in the center of the solid electrolyte layer is 3% or less, the porosity near the ends can also be made relatively low. In addition, -2 μm 2 By reducing the number of larger voids to 10% or less of the total voids, the solid electrolyte layer can be made homogenous. This makes it possible to make the battery reaction more uniform. As a result, an all-solid-state secondary battery with excellent load characteristics can be obtained. This effect can contribute, for example, to Goal 7 "Affordable and clean energy" and Goal 12 "Responsible consumption and production" of the Sustainable Development Goals (SDGs) advocated by the United Nations.

[0019] As a rough guide, the region of the SEM image for calculating the porosity and number ratio (the region including the center in the width direction and the center in the thickness direction of the cross section of the solid electrolyte layer, i.e., the center portion) is a rectangular region with a width length of 25 μm and a thickness length of 19 μm. When the thickness of the solid electrolyte layer is approximately 24 μm or less, the thickness length of the rectangular region is reduced according to the thickness of the solid electrolyte layer. In this case, the thickness length of the rectangular region is set to 80% of the thickness of the solid electrolyte layer so that the rectangular region does not include the region near the positive electrode side interface and the region near the negative electrode side interface of the solid electrolyte layer. This can reduce the variation in the measurement.

[0020] The positive electrode may have a molded body of a positive electrode mixture containing a positive electrode active material powder, a conductive assistant, and a solid electrolyte. The solid electrolyte of the positive electrode mixture may include, for example, a sulfide-based solid electrolyte. The positive electrode active material powder may be composed of, for example, a powder of primary particles containing a positive electrode active material. In this case, the positive electrode active material powder may be, for example, primary particles having a lithium ion conductive coating material formed on the surface of the positive electrode active material.

[0021] The negative electrode may have a molded body of a negative electrode mixture containing a negative electrode active material powder, a conductive additive, and a solid electrolyte. The solid electrolyte of the negative electrode mixture may include, for example, a sulfide-based solid electrolyte.

[0022] The method for producing the all-solid-state secondary battery includes a step of pressurizing and molding a layered assembly of sulfide-based solid electrolyte particles at a surface pressure of 1000 MPa or more. This allows the porosity of the central part of the solid electrolyte layer to be 3% or less and 1×10 -2 μm 2 It is possible to efficiently manufacture an all-solid-state secondary battery having a solid electrolyte layer in which the proportion of larger voids is 10% or less in terms of number ratio.

[0023] The manufacturing method may further include a step of stacking the positive electrode, the negative electrode, and the solid electrolyte layer. In this case, the solid electrolyte layer is stacked so as to be disposed between the positive electrode and the negative electrode. The step of pressurizing the layered assembly of sulfide-based solid electrolyte particles with a surface pressure of 1000 MPa or more may be a step of pressurizing the layered assembly of sulfide-based solid electrolyte particles in a state in which the layered assembly is stacked on at least one of the positive electrode and the negative electrode. Alternatively, the layered assembly of sulfide-based solid electrolyte particles may be pressurized before being stacked on the positive electrode and the negative electrode.

[0024] Hereinafter, the embodiments will be described in detail. In the drawings, the same or corresponding components are denoted by the same reference numerals, and the same description will not be repeated. In order to make the description easier to understand, the drawings referred to below may show the components in a simplified or schematic manner, or some components may be omitted.

[0025] (positive electrode) The positive electrode of the all-solid-state secondary battery has a molded body of a positive electrode mixture containing a positive electrode active material, a conductive assistant, a solid electrolyte, and the like, and can be composed of, for example, only the molded body, or can be composed by integrating the molded body with a current collector.

[0026] The positive electrode active material is not particularly limited as long as it is a positive electrode active material used in conventionally known lithium ion secondary batteries, that is, an active material capable of absorbing and releasing Li ions, and such positive electrode active materials may be used alone or in combination of two or more kinds. For example, LiM x Mn 2-x O 4 (wherein M is at least one element selected from the group consisting of Li, B, Mg, Ca, Sr, Ba, Ti, V, Cr, Fe, Co, Ni, Cu, Al, Sn, Sb, In, Nb, Mo, W, Y, Ru, and Rh, and 0.01≦x≦0.5), a spinel-type lithium manganese-containing oxide represented by the formula: Li x Ni (1-y-z) Co y M z O (2-k) F l(wherein M is at least one element selected from the group consisting of Mn, Mg, Al, B, Ti, V, Cr, Fe, Cu, Zn, Zr, Mo, Sn, Ca, Sr, and W, and 0.8≦x≦1.2, 0≦y<0.5, 0≦z<0.5, k+l<1, -0.1≦k≦0.2, 0≦l≦0.1), lithium nickel-containing oxide having a layered structure represented by Li x Co (1-y) M y O (2-k) F l (wherein M is at least one element selected from the group consisting of Ni, Mn, Mg, Al, B, Ti, V, Cr, Fe, Cu, Zn, Zr, Mo, Sn, Ca, Sr, and W, and 0.8≦x≦1.2, 0≦y≦0.2, k+l<1, -0.1≦k≦0.2, 0≦l≦0.1), lithium cobalt-containing oxide having a layered structure represented by the formula LiM 1-x Q x PO 4 (wherein M is at least one element selected from the group consisting of Fe, Mn, and Co, and Q is at least one element selected from the group consisting of Al, Mg, Ti, Zr, Ni, Cu, Zn, Ga, Ge, Nb, Mo, Sn, Sb, and Ba, and 0≦x≦0.5).

[0027] In order to meet the demands of high-voltage batteries, it is preferable that the positive electrode active material contains a layered lithium-cobalt-containing oxide.

[0028] When a sulfide-based solid electrolyte is used as the solid electrolyte of the positive electrode, it is desirable to form a lithium ion conductive coating material, which is unlikely to react with the sulfide-based solid electrolyte, on the surface of the positive electrode active material in order to prevent a direct reaction between the solid electrolyte and the positive electrode active material. The lithium ion conductive coating material is LiNbO 3 Lithium niobium-containing oxides such as the above are preferably used.

[0029] When the positive electrode mixture is pressure-molded into a molded body, or when a layered assembly of sulfide-based solid electrolyte particles is pressure-molded to form a solid electrolyte layer, the positive electrode active material is desirably in the form of a powder of primary particles (positive electrode active material powder) so that cracks and the like are unlikely to occur in the molded body of the positive electrode mixture even when a high pressure is applied.

[0030] The positive electrode active material powder can be, for example, a powder of primary particles in which a lithium ion conductive coating material is formed on the surface of the positive electrode active material.

[0031] If the average particle size of the positive electrode active material powder composed of primary particles having a lithium ion conductive coating material formed on the surface becomes too large, the particles may crack when pressed under high pressure, causing the core material to come into contact with the solid electrolyte. Therefore, the average particle size of the positive electrode active material powder is preferably 8 μm or less, more preferably 6 μm or less.

[0032] On the other hand, if the average particle diameter of the positive electrode active material powder is too small, it becomes bulky and difficult to pack densely, resulting in a decrease in the capacity of the positive electrode. Therefore, the average particle diameter of the positive electrode active material powder is preferably 1 μm or more, and more preferably 3 μm or more.

[0033] By using a positive electrode active material powder constituted by primary particles having an average particle size within the above range, the porosity of the positive electrode mixture compact can be easily adjusted to 10% or less by volume.

[0034] The average particle diameter of the positive electrode active material powder can be measured using a particle size distribution measuring device (such as Microtrac's "MT3300EXII" particle size distribution measuring device manufactured by Microtrac-Bell, Inc.), and is determined as the 50% diameter value (d50) in the volume-based integrated fraction when determining the integral volume from particles with small particle sizes. The same applies to the negative electrode active material and the solid electrolyte.

[0035] The positive electrode active material powder made of the primary particles may be a commercially available product. The positive electrode active material powder is preferably made of only primary particles, but may also contain some secondary particles. However, in order to prevent the above-mentioned problems, the proportion of secondary particles in the positive electrode active material powder is preferably 30% by mass or less, more preferably 15% by mass or less, and particularly preferably 10% by mass or less.

[0036] The lithium ion conductive coating material can be formed on the surface of the positive electrode active material by a sol-gel method, a mechanofusion method, a CVD method, a PVD method, or the like.

[0037] The amount of the lithium ion conductive coating material formed is preferably such that the ratio of the coating material to the entire positive electrode active material including the coating material is 0.1% by mass or more, more preferably 0.5% by mass or more, in order to increase the surface coverage of the positive electrode active material and facilitate its action. On the other hand, if the amount of the lithium ion conductive coating material formed is too large, the capacity per unit weight of the positive electrode active material powder decreases, so the ratio of the coating material to the entire positive electrode active material is preferably 5% by mass or less, more preferably 2% by mass or less.

[0038] The content of the positive electrode active material powder in the positive electrode mixture is 65% by mass or more, preferably 70% by mass or more, in order to increase the capacity of the positive electrode. On the other hand, in order to make the content of the solid electrolyte and the conductive assistant in the positive electrode mixture at a certain level or more and to make the positive electrode mixture excellent in ionic conductivity and electronic conductivity, the content of the positive electrode active material powder in the positive electrode mixture is 85% by mass or less, preferably 80% by mass or less.

[0039] As the conductive assistant for the positive electrode, carbon materials such as graphite (natural graphite, artificial graphite), graphene, carbon black, vapor grown carbon fiber (VGCF), carbon nanofiber, and carbon nanotube can be used.

[0040] For the solid electrolyte of the positive electrode, it is desirable to use a sulfide-based solid electrolyte in order to enhance ion conductivity. Examples of sulfide-based solid electrolytes include compounds composed of Li, S, and P, and optionally halogen elements or Si that serve as constituent elements. For example, Li 2 S-P 2 S 5 、Li 2 S-SiS 2 、Li 2 S-P 2 S 5 -GeS 2 、Li 2 S-B 2 S 3 -based glass; Li 10 GeP 2 S 12 (LGPS-based); Li 7+x P 1-y Si y S 6 (-0.6 ≦ x ≦ 0.6, 0.1 ≦ y ≦ 0.6), Li 7-x+y PS 6-x Cl x+y (0.05 ≦ y ≦ 0.9, -3x + 1.8 ≦ y ≦ -3x + 5.7), Li 7-x PS 6-x Cl y Br z (x = y + z, 1 < x ≦ 1.8, 0.1 ≦ z / y ≦ 10), etc. Among them, compounds having an argyrodite-type crystal structure such as Li 7-x+y PS 6-x Cl x+y (0.05 ≦ y ≦ 0.9, -3x + 1.8 ≦ y ≦ -3x + 5.7), Li 7-x PS 6-x Cl y Br z (x = y + z, 1 < x ≦ 1.8, 0.1 ≦ z / y ≦ 10) are more preferred, and Li 7-x+y PS 6-x Cl x+y (0.05 ≦ y ≦ 0.9, -3x + 1.8 ≦ y ≦ -3x + 5.7) is particularly preferably used.

[0041] The average particle size of the sulfide-based solid electrolyte is preferably 0.1 μm or more, more preferably 0.5 μm or more, and is preferably 5 μm or less, in order to increase the filling property of the positive electrode mixture compact having the positive electrode active material powder of the above particle size and reduce the porosity.

[0042] The positive electrode mixture may contain other solid electrolytes together with or instead of the sulfide-based solid electrolyte. Examples of the other solid electrolytes than the sulfide-based solid electrolyte include hydride-based solid electrolytes and oxide-based solid electrolytes.

[0043] Examples of hydride-based solid electrolytes include LiBH 4 , L.B.H. 4 and the following alkali metal compounds (e.g., LiBH 4 and the alkali metal compound in a molar ratio of 1:1 to 20:1. Examples of the alkali metal compound in the solid solution include lithium halides (LiI, LiBr, LiF, LiCl, etc.), rubidium halides (RbI, RbBr, RbiF, RbCl, etc.), cesium halides (CsI, CsBr, CsF, CsCl, etc.), lithium amide, rubidium amide, cesium amide, etc.

[0044] As an oxide-based solid electrolyte, for example, Li 7 La 3 Zr 2 O 12 , LiTi(PO 4 ) 3 , LiGe(PO 4 ) 3 , LiLaTiO 3 etc.

[0045] However, in order to prevent a decrease in the ionic conductivity or moldability of the positive electrode mixture, the proportion of solid electrolytes other than the sulfide-based solid electrolyte in the total amount of solid electrolytes used in the positive electrode mixture is preferably 30 mass% or less, more preferably 10 mass% or less, and particularly preferably contains no other solid electrolytes.

[0046] The content of the solid electrolyte in the positive electrode mixture is preferably 15% by mass or more, and more preferably 20% by mass or more, in order to enhance ion conductivity, while it is preferably 35% by mass or less, and more preferably 30% by mass or less, in order to ensure the content of the positive electrode active material powder.

[0047] The positive electrode mixture may contain a resin binder as necessary. Examples of the resin binder include fluororesins such as polyvinylidene fluoride (PVDF) and acrylic resins such as acrylic acid-acrylic acid ester copolymers. However, since the resin binder acts as a resistance component in the positive electrode mixture, it is desirable to reduce the amount of the resin binder as much as possible when the resin binder is contained, and the content is preferably 0.5 mass% or less, more preferably 0.3 mass% or less, and most preferably 0 mass% (i.e., no resin binder is contained).

[0048] When a current collector is used for the positive electrode, the current collector can be made of a metal foil such as aluminum or stainless steel, a punched metal, a net, an expanded metal, a foamed metal, a carbon sheet, or the like.

[0049] From the viewpoint of increasing the capacity of the battery, the thickness of the positive electrode mixture compact is preferably 200 μm or more, and more preferably 500 μm or more. On the other hand, from the viewpoint of facilitating the formation of a compact with a low porosity and improving the load characteristics, the thickness of the positive electrode mixture compact is preferably 2 mm or less, and more preferably 1.2 mm or less.

[0050] In the case of a positive electrode having a current collector, the thickness of the positive electrode mixture molded body per one surface of the current collector may be within the above range.

[0051] (Negative electrode) The negative electrode of the all-solid-state secondary battery has a molded body of a negative electrode mixture containing a negative electrode active material, a conductive assistant, a solid electrolyte, and the like, and can be composed of, for example, only the molded body, or can be composed by integrating the molded body with a current collector.

[0052] As the negative electrode active material, for example, one or a mixture of two or more of carbon-based materials capable of absorbing and releasing lithium, such as graphite, pyrolytic carbons, cokes, glassy carbons, baked bodies of organic polymer compounds, mesocarbon microbeads (MCMB), carbon fibers, etc., can be used. In addition, elements such as Si, Sn, Ge, Bi, Sb, In, and Al that can form an alloy with lithium, alloys of the above elements with elements that do not form an alloy with lithium, and compounds such as oxides of the above elements; lithium-containing nitrides; composite oxides such as lithium titanium oxide having a spinel structure; and lithium metal can also be used as the negative electrode active material.

[0053] The content of the negative electrode active material in the negative electrode mixture is preferably 45% by mass or more, more preferably 50% by mass or more, in order to increase the capacity of the negative electrode, while the content of the solid electrolyte and the conductive assistant in the negative electrode mixture is set to a certain level or more, in order to improve the ionic conductivity and electronic conductivity of the negative electrode mixture, the content of the negative electrode active material in the negative electrode mixture is preferably 65% ​​by mass or less, more preferably 60% by mass or less.

[0054] As the conductive additive for the negative electrode, carbon materials such as graphite (natural graphite, artificial graphite), graphene, carbon black, carbon nanofibers, carbon nanotubes, etc. can be used. From the viewpoint of improving the electron conductivity in the molded body of the negative electrode mixture, the content of the conductive additive in the negative electrode mixture is preferably 5% by mass or more, more preferably 7% by mass or more. Also, if the amount of the conductive additive in the negative electrode mixture is too large, voids tend to increase in the molded body of the negative electrode mixture, making it difficult to increase its packing rate, and there is a risk that the volume energy density of the all-solid-state secondary battery will decrease. Therefore, from the viewpoint of reducing the porosity of the molded body of the negative electrode mixture, the content of the conductive additive in the negative electrode mixture is preferably 15% by mass or less, more preferably 12% by mass or less.

[0055] For the solid electrolyte of the negative electrode as well, in order to enhance the ionic conductivity, it is desirable to use a sulfide-based solid electrolyte. As the sulfide-based solid electrolyte, the same solid electrolytes as those exemplified as the sulfide-based solid electrolytes usable for the positive electrode mixture can be used, but compounds having an argyrodite-type crystal structure with higher ionic conductivity are preferably used. Li 7-x PS 6-x Cl y Br z (x = y + z, 1 < x ≤ 1.8, 0.1 ≤ z / y ≤ 10) is more preferably used. By using the solid electrolyte, the porosity of the negative electrode mixture during the subsequent pressure molding can be, for example, 20% or less, preferably 15% or less.

[0056] The negative electrode mixture may contain another solid electrolyte together with the sulfide-based solid electrolyte or in place of the sulfide-based solid electrolyte. Examples of the other solid electrolytes than the sulfide-based solid electrolyte include hydride-based solid electrolytes, oxide-based solid electrolytes, etc. The same solid electrolytes as those exemplified for the positive electrode mixture can be used for these solid electrolytes.

[0057] However, in order to prevent a decrease in the ionic conductivity or moldability of the negative electrode mixture, the proportion of solid electrolytes other than the sulfide-based solid electrolyte in the total amount of solid electrolytes used in the negative electrode mixture is preferably 30 mass% or less, more preferably 10 mass% or less, and particularly preferably contains no other solid electrolytes.

[0058] The content of the solid electrolyte in the negative electrode mixture is preferably 35 mass % or more, and more preferably 40 mass % or more, in order to enhance ion conductivity, while it is preferably 55 mass % or less, and more preferably 50 mass % or less, in order to ensure the content of the negative electrode active material.

[0059] The negative electrode mixture may contain a resin binder as necessary. Examples of the resin binder include fluororesins such as polyvinylidene fluoride (PVDF) and acrylic resins such as acrylic acid-acrylic acid ester copolymers. However, since the resin binder acts as a resistance component in the negative electrode mixture, it is desirable to reduce the amount of the resin binder as much as possible when the resin binder is contained, and the content is preferably 0.5 mass% or less, more preferably 0.3 mass% or less, and most preferably 0 mass% (i.e., no resin binder is contained).

[0060] When a current collector is used for the negative electrode, the current collector can be made of copper or nickel foil, punched metal, net, expanded metal, foamed metal; carbon sheet; or the like.

[0061] The thickness of the negative electrode mixture compact is preferably 200 μm or more, more preferably 500 μm or more, from the viewpoint of increasing the capacity of the battery. On the other hand, from the viewpoint of facilitating the formation of a compact with a low porosity and improving the load characteristics, the thickness of the negative electrode mixture compact is preferably 3 mm or less, more preferably 2 mm or less. In the case of a negative electrode having a current collector, the thickness of the negative electrode mixture compact per one side of the current collector may be within the above range.

[0062] (Solid electrolyte layer) In the solid electrolyte of the solid electrolyte layer of the all-solid-state secondary battery, a sulfide-based solid electrolyte is used to enhance ion conductivity. As the sulfide-based solid electrolyte, the same solid electrolyte as exemplified as the sulfide-based solid electrolyte that can be used for the positive electrode mixture can be used, but a compound having an argyrodite-type crystal structure with higher ion conductivity is preferably used. Li 7-x PS 6-x Cl y Br z (x = y + z, 1 < x ≤ 1.8, 0.1 ≤ z / y ≤ 10) is more preferably used.

[0063] The sulfide-based solid electrolyte desirably has an average particle diameter of 0.3 to 1.5 μm in order to reduce the porosity during pressure molding and to facilitate molding.

[0064] Note that the solid electrolyte layer may be composed of only one layer, but it can also have a laminated structure. The layer in contact with the positive electrode is composed of a highly stable sulfide-based solid electrolyte, for example, Li 7-x+y PS 6-x Cl x+y (0.05 ≤ y ≤ 0.9, -3x + 1.8 ≤ y ≤ -3x + 5.7), and the layer on the negative electrode side can be composed of a sulfide-based solid electrolyte having high ion conductivity, for example, Li 7-x PS 6-x Cl y Br z (x = y + z, 1 < x ≤ 1.8, 0.1 ≤ z / y ≤ 10).

[0065] Furthermore, the solid electrolyte layer may have a porous body such as a resin nonwoven fabric as a support.

[0066] The solid electrolyte layer may contain other solid electrolytes together with the sulfide-based solid electrolyte. In order to prevent the ion conductivity or moldability of the solid electrolyte layer from decreasing, the content of the solid electrolyte other than the sulfide-based solid electrolyte in the solid electrolyte layer is preferably 30 mass % or less, more preferably 10 mass % or less, and particularly preferably does not contain other solid electrolytes.

[0067] In order to ensure insulation between the positive and negative electrodes, the thickness of the solid electrolyte layer is preferably 10 μm or more, more preferably more than 20 μm, and even more preferably 50 μm or more, while in order to reduce the internal resistance of the battery, the thickness of the solid electrolyte layer is preferably 300 μm or less, and more preferably 200 μm or less.

[0068] (Laminated electrode body) The molded body of the positive electrode mixture is, for example, composed of a positive electrode mixture prepared by mixing a positive electrode active material powder, a conductive assistant, a solid electrolyte, and a binder added as necessary, and can be formed by putting the positive electrode mixture into a mold to form a layer of a predetermined thickness, and then compressing it by pressure molding, etc. The molded body of the negative electrode mixture is, for example, composed of a negative electrode mixture prepared by mixing a negative electrode active material, a conductive assistant, a solid electrolyte, and a binder added as necessary, and can be formed by putting the negative electrode mixture into a mold to form a layer of a predetermined thickness, and then compressing it by pressure molding, etc.

[0069] The positive electrode mixture compact and the negative electrode mixture compact are used as electrodes (positive electrode and negative electrode) as they are or are attached to a current collector by a method such as pressure bonding.

[0070] The solid electrolyte layer can be formed, for example, by putting solid electrolyte particles into a mold to form a layer (a layered assembly of solid electrolyte particles) of a predetermined thickness, and then compressing the layer in the thickness direction by pressure molding or the like, and the molded body is used for assembling a battery. The pressure during pressurization may be 1000 MPa or more in terms of surface pressure. This can reduce the porosity of the solid electrolyte layer and the size of the voids, and a desired solid electrolyte layer can be formed. When pressurization is performed multiple times during the formation of the solid electrolyte layer, the pressure during one of the pressurizations may be 1000 MPa or more in terms of surface pressure. The pressure during pressurization of the layered assembly of solid electrolyte particles may be 1200 MPa or more.

[0071] In addition, the solid electrolyte particles may be dispersed in a solvent and used in the form of a paint to form the solid electrolyte layer. The paint may be applied onto a substrate, a positive electrode mixture, or a negative electrode mixture, dried to form a layered aggregate having a predetermined thickness, and then pressure molded.

[0072] It is preferable to select a solvent that does not deteriorate the solid electrolyte when used to prepare the paint for the solid electrolyte. In particular, since sulfide-based solid electrolytes and hydride-based solid electrolytes undergo chemical reactions with a small amount of water, it is preferable to use a non-polar aprotic solvent represented by a hydrocarbon solvent such as hexane, heptane, octane, nonane, decane, decalin, toluene, or xylene. In particular, it is more preferable to use an ultra-dehydrated solvent with a water content of 0.001 mass% (10 ppm) or less. In addition, fluorine-based solvents such as "Vertrel (registered trademark)" manufactured by Mitsui DuPont Fluorochemicals, "Zeorolla (registered trademark)" manufactured by Nippon Zeon Co., Ltd., and "Novec (registered trademark)" manufactured by Sumitomo 3M Co., Ltd., as well as non-aqueous organic solvents such as dichloromethane and diethyl ether can also be used.

[0073] The positive electrode mixture compact and the negative electrode mixture compact are laminated and integrated with a solid electrolyte layer interposed therebetween to form a laminated electrode body, which is used for assembling a battery.

[0074] The conditions for producing the positive electrode mixture compact can be, for example, as follows.

[0075] A positive electrode active material powder consisting of primary particles with an average particle size of 1 to 8 μm is mixed with a sulfide-based solid electrolyte with an average particle size of 0.1 to 5 μm to prepare a positive electrode mixture containing the positive electrode active material powder in a ratio of 65 to 85 mass %. This is then placed in a mold to form a layer of a predetermined thickness, and pressed to produce a positive electrode mixture compact. The pressure during pressing is 1000 MPa (10 ton / cm) as a surface pressure. 2 This makes it easy to achieve a porosity of 10% or less in the molded body.

[0076] The negative electrode mixture compact can be produced under the same conditions as those for producing the positive electrode mixture compact, and the pressure during pressing is 1000 MPa (10 ton / cm) as the surface pressure. 2 ) or more, the filling rate can be increased.

[0077] The layer of the positive electrode mixture and the layer of the negative electrode mixture may be pressed in one go, but they may also be pressed at a pressure of less than 1000 MPa to increase the filling rate of the mixture to a certain degree, and then further pressed at a pressure of 1000 MPa or more to form the desired molded body.

[0078] The order in which the layers are stacked is not limited. For example, a layer of the negative electrode mixture may be formed first, a layer of the solid electrolyte powder may be formed thereon, and a layer of the positive electrode mixture may be formed thereon to form a laminate. Alternatively, a layer of the solid electrolyte powder may be formed first, one layer of the negative electrode mixture and the positive electrode mixture may be formed on one side of the layer of the solid electrolyte powder, and the other layer of the negative electrode mixture and the positive electrode mixture may be formed on the other side of the layer of the solid electrolyte powder to form a laminate.

[0079] Alternatively, the positive electrode mixture compact, the solid electrolyte layer, and the negative electrode mixture compact may be separately prepared in advance, and then finally laminated and integrated. For example, the positive electrode mixture compact, the solid electrolyte layer, and the negative electrode mixture compact may each be separately prepared in advance by pressure molding.

[0080] There is no lower limit for the porosity of the positive electrode mixture compact, and the lower the value, the better. However, due to restrictions on the manufacturing equipment and in consideration of productivity, the pressure when pressing the positive electrode mixture compact is usually set to 2000 MPa (20 ton / cm) as the surface pressure. 2 ) so that the porosity of the positive electrode mixture compact that is actually obtained is 3~ The lower limit is around 5%.

[0081] The porosity of the positive electrode mixture compact referred to in this specification is a value calculated by determining the sum for each component i using the following formula (1) from the thickness of the positive electrode mixture compact, the mass per area, and the density of the constituent components.

[0082] P = 100-(Σai / ρi)×(m / t) (1)

[0083] In the above formula (1), ai: the ratio of component i expressed in mass%, ρi: the density of component i (g / cm 3 ), m: mass per unit area of ​​the positive electrode mixture compact (g / cm 2 ), t: thickness (cm) of the positive electrode mixture compact.

[0084] Alternatively, the cross sections of the positive electrode mixture and negative electrode mixture molded bodies may be observed by a scanning electron microscope (SEM), the proportion of voids may be determined by image processing, and the porosity of the positive electrode mixture molded body may be calculated. In this case, it is desirable to determine the conditions of the image processing so that the value is consistent with the porosity determined by the above method.

[0085] The porosity of the solid electrolyte layer is measured as follows. The solid electrolyte layer is cut along a plane parallel to the thickness direction, passing through the center of the longest width when viewed from the thickness direction, and an SEM image (backscattered electron image) of a rectangular region (center) including the center of the cross section of the layer (center of the thickness direction and center of the width direction) with a width length of 25 μm and a thickness length of 19 μm is obtained for the portion between the positive and negative electrodes. This SEM image is binarized using image analysis software (ImageJ, etc.), and the bright contrast (high brightness) is regarded as material and the dark contrast (low brightness) as voids, and the porosity is calculated by determining the area ratio of the voids.

[0086] The equipment and conditions used can be, for example, as follows: Scanning electron microscope: Hitachi S4800 Detector: Backscattered electron enhancement mode Acceleration voltage: 2 kV Magnification: 5,000x Capture resolution: 2,560 x 1,920 Minimum dot length: 9.9 nm (equivalent circle diameter: 11.2 nm) Minimum dot area: 98nm 2 Analysis area: 4.81×10 8 nm 2

[0087] The obtained SEM image is converted to grayscale using Photoshop (registered trademark). At this time, a Gaussian filter (0.5 pixels) is used to reduce noise. Next, the histogram of the SEM image is quantified using ImageJ. FIG. 2 is a diagram showing an example of a histogram of an SEM image. In the histogram, the brightness: a at the maximum frequency is set as the median value. On the higher brightness side than the median value, the brightness: b at a frequency where the numerical value is 3% of the maximum frequency is read, and further, on the lower brightness side than the median value, the brightness: d (= a - b) where the numerical value is smaller than the median value by the difference between b and a: c (= ba) is obtained, and the brightness d is set as the threshold value.

[0088] Furthermore, the image analysis software "Eizou-kun" binarizes the SEM image using the previously obtained threshold value d to separate the image into low-brightness and high-brightness areas. The ratio of the area of ​​the low-brightness area in the SEM image is calculated as the porosity. 2 (0.09×10 -2 μm 2 ) are judged to be noise components, so they are excluded from the void area (low-brightness area after noise components are removed) to calculate the void ratio. -2 μm 2 Calculate the ratio of the frequency (number) of larger voids to the frequency (number) of all voids in the SEM image. This ratio is calculated as the ratio of 1×10 to the frequency (number) of all voids in the SEM image. -2 μm 2 The larger the void ratio, the

[0089] The size of the rectangular region for acquiring the SEM image (backscattered electron image) can be changed according to the thickness of the solid electrolyte layer when the solid electrolyte layer is thin. When the thickness of the solid electrolyte layer is about 24 μm or less, the length in the thickness direction of the rectangular region may be set to 80% of the thickness of the solid electrolyte layer so that the rectangular region does not include the region near the positive electrode side interface and the region near the negative electrode side interface of the solid electrolyte layer.

[0090] The porosity of the central portion of the cross section of the solid electrolyte layer measured as described above is 3% or less, and the porosity of the central portion of the cross section of the solid electrolyte layer is 1×10 -2 μm 2 The solid electrolyte layer is formed so that the ratio of larger voids is 10% or less in terms of number ratio. This makes it possible to make the reaction of the all-solid-state battery more uniform and improve the load characteristics. The porosity of the central part of the cross section of the solid electrolyte layer measured as described above is more preferably 2% or less, and even more preferably 1% or less. The ratio of 1×10 pores to all pores in that region is 1×10 pores. -2 μm 2 More preferably, the proportion of larger voids is 8% or less, and even more preferably, 5% or less.

[0091] At least one of the positive electrode mixture, the negative electrode mixture, and the composition for forming the solid electrolyte layer may be pressure molded in a heated state. By molding the solid electrolyte material in a heated and softened state, the contact area between the active material and the solid electrolyte material or between the solid electrolyte materials themselves increases, and the filling property of the molded body can be improved.

[0092] The heating temperature depends on the composition of the solid electrolyte material, but can be, for example, 60 to 200°C.

[0093] (Battery type) The all-solid-state secondary battery of the present invention can be configured as, for example, a coin-type battery. Fig. 1 is a schematic cross-sectional view of a coin-type battery, and the battery 1 shown in Fig. 1 has a positive electrode 10, a negative electrode 20, and a solid electrolyte layer 30 interposed between the positive electrode 10 and the negative electrode 20 enclosed in an exterior body formed of an exterior can 40, a sealing can 50, and a resin gasket 60 interposed between them.

[0094] The sealing can 50 is fitted into the opening of the outer can 40 via a gasket 60, and the open end of the outer can 40 is tightened inward, whereby the gasket 60 comes into contact with the sealing can 50, sealing the opening of the outer can 40 and forming an airtight structure inside the element.

[0095] The outer can and the sealing can can be made of stainless steel or the like. The gasket can be made of polypropylene, nylon, or other materials. If heat resistance is required for the battery's intended use, heat-resistant resins with melting points exceeding 240°C, such as fluororesins such as tetrafluoroethylene-perfluoroalkoxyethylene copolymer (PFA), polyphenylene ether (PEE), polysulfone (PSF), polyarylate (PAR), polyethersulfone (PES), polyphenylene sulfide (PPS), and polyetheretherketone (PEEK), can also be used. If the battery is used in an application that requires heat resistance, a glass hermetic seal can be used for the sealing.

[0096] The form of the all-solid-state secondary battery is not limited to a flat shape having an exterior body composed of an exterior can, a sealing can, and a gasket as shown in Fig. 1. For example, the all-solid-state secondary battery may have an exterior body composed of a resin film or a metal-resin laminate film. Alternatively, the all-solid-state secondary battery may have an exterior body having a metallic exterior can having a bottomed tubular shape (cylindrical or rectangular tubular shape) and a sealing structure that seals the opening of the can.

[0097] The all-solid-state secondary battery of the present invention can be used for the same applications as conventionally known secondary batteries, but since it has a solid electrolyte instead of an electrolytic solution, it has excellent heat resistance and can be preferably used for applications in which it is exposed to high temperatures. EXAMPLES

[0098] The present invention will be described in detail below based on examples, but the present invention is not limited to the following examples.

[0099] Example 1 <Preparation of laminated electrode body> LiNbO 3 The LiCoO coating layer was formed. 2 The positive electrode active material powder (average particle size: 5 μm) is made up of primary particles of Li and the sulfide-based solid electrolyte (average particle size: 3 μm) is made up of Li 7.0 P.S. 5.4 Cl 1.2 The positive electrode mixture was prepared by mixing the carbon black and the vapor grown carbon fiber (VGCF) in a mass ratio of 70:26.8:1.1:2.1 and thoroughly kneading the mixture. The weight ratio of Nb in the coating layer to the weight of the positive electrode active material powder was 2 mass%.

[0100] In addition, lithium titanate (Li 4 Ti 5 O 12 , negative electrode active material) and a sulfide-based solid electrolyte with an average particle size of 0.7 μm: Li 5.4 P.S. 4.4 Cl 0.8 Br 0.8and graphene (conductive assistant) in a mass ratio of 50:41:9, and thoroughly kneaded to prepare a negative electrode mixture.

[0101] Next, 92 mg of the positive electrode mixture was placed in a powder molding die and pressed at 100 MPa (1 ton / cm 2 The positive electrode mixture was pressed at a pressure of 10 ... 5.4 P.S. 4.4 Cl 0.8 Br 0.8 16 mg of powder was added and the mixture was pressed at 100 MPa (1 ton / cm 2 Further, 129 mg of the negative electrode mixture was placed on the formed sulfide-based solid electrolyte to form a three-layer laminate, and then the laminate was pressed at a pressure of 1200 MPa (12 ton / cm) using a press machine. 2 ) to produce a laminated electrode body consisting of a positive electrode (a positive electrode mixture compact having a thickness of 0.68 mm) / solid electrolyte layer (thickness: 0.19 mm) / negative electrode (a negative electrode mixture compact having a thickness of 1.24 mm).

[0102] In the laminated electrode body, the porosity of the positive electrode mixture compact was 8%, and the porosity of the negative electrode mixture compact was 10%. In addition, the size (area) and distribution of individual voids were determined by performing the above-mentioned image processing on an SEM image taken at a magnification of 5000 times for the central portion of the cross section of the solid electrolyte layer. The results are shown in Figure 3. The size determined by image processing was 0.09 × 10 -2 μm 2 The smaller ones are actually not voids but noise, and were therefore excluded from the results. Figure 4(a) shows the SEM image after image processing in Example 1, which has been divided into low-brightness and high-brightness areas by binarization.

[0103] From this result, the sum of the areas of the individual voids was calculated for the central portion of the cross section of the solid electrolyte layer of Example 1, and the ratio to the area of ​​the solid electrolyte layer was calculated as the porosity, which was calculated to be 1.0%. -2 μm2 The percentage of larger voids was 3.8%.

[0104] <Battery assembly> A stainless steel sealing can and exterior can were used as the exterior body, and a porous carbon sheet having a thickness of 0.1 mm was placed between the sealing can and the exterior can and between the laminated electrode body, respectively, to seal the battery, thereby producing a coin-type all-solid-state secondary battery.

[0105] Comparative Example 1 After forming the three-layer laminate, the pressure for press molding was set to 600 MPa (6 ton / cm 2 ) A laminated electrode body was produced in the same manner as in Example 1. In the laminated electrode body, the porosity of the positive electrode mixture compact was 15%, and the porosity of the negative electrode mixture compact was 16%.

[0106] In addition, the size (area) of each void and its distribution were determined by image processing of an SEM image obtained at a magnification of 5000 times for the central part of the cross section of the solid electrolyte layer, and the results are shown in Fig. 3 together with those of Example 1. Fig. 4(b) is an SEM image after image processing in Comparative Example 1, which has been divided into low brightness areas and high brightness areas by binarization.

[0107] From this result, the calculated porosity of the central part of the cross section of the solid electrolyte layer of Comparative Example 1 was 5.8%, and the size of the voids relative to the number of all voids was 1×10 -2 μm 2 The percentage of the number of larger voids was 12.9%. Thereafter, a coin-type all-solid-state secondary battery was assembled in the same manner as in Example 1.

[0108] The all-solid-state secondary batteries of the Examples and Comparative Examples were subjected to the following evaluations. <Load characteristic evaluation> The produced batteries of the examples and comparative examples were subjected to constant current-constant voltage charging, which combines constant current charging at a current value of 0.2 C until the battery voltage reached 3.1 V and constant voltage charging at a voltage of 3.1 V until the current value reached 0.02 C, and then constant current discharging was performed at a current value of 0.1 C until the battery voltage reached 1.2 V, and the discharge capacity at 0.1 C was measured. The evaluation results are shown in Table 1.

[0109] [Table 1]

[0110] In the all-solid-state secondary battery of Example 1, the porosity of the solid electrolyte layer is set to 3% or less, and the total voids are occupied by 1×10 -2 μm 2 By increasing the proportion of larger voids to 10%, the battery had excellent load characteristics.

[0111] On the other hand, in the all-solid-state secondary battery of Comparative Example 1, the porosity of the solid electrolyte layer exceeded 3%, and 1×10 -2 μm 2 The proportion of larger voids was also greater than 10%, resulting in a decrease in load characteristics compared to the battery of Example 1. [Explanation of symbols]

[0112] 1 All-solid-state secondary battery 10 positive electrode 20 negative electrode 30 Solid electrolyte layer 40 Outer can 50 sealed cans 60 Gasket

Claims

1. An all-solid-state secondary battery having a positive electrode, a negative electrode, and a solid electrolyte layer containing a sulfide-based solid electrolyte disposed between the positive electrode and the negative electrode, The porosity of the solid electrolyte layer calculated from a scanning electron microscope (SEM) image of the central portion of the cross section of the solid electrolyte layer is 3% or less, and the porosity of the solid electrolyte layer is 1×10 occupying all the voids in the region. -2 μm 2 An all-solid-state secondary battery, in which the ratio of larger voids is 10% or less in terms of number.

2. A method for producing the all-solid-state secondary battery according to claim 1, A method for producing an all-solid-state secondary battery, comprising the step of press-molding a layered assembly of sulfide-based solid electrolyte particles at a surface pressure of 1000 MPa or more.

Citation Information

Patent Citations

  • Lithium solid type secondary battery, and method for manufacturing the same

    JP2016012495A

  • All-solid battery and method for manufacturing the same

    JP2018120709A

  • Solid-state secondary battery and manufacturing method of all-solid secondary battery

    JP2018206469A

  • Solid electrolyte sheet, negative electrode sheet for all-solid type secondary battery and all-solid type secondary battery, and manufacturing methods thereof

    JP2020107594A

  • All-solid-state batteries, electronic devices, electronic cards, wearable devices and electric vehicles

    JP6729796B2